The perception of Malaysian consumers on the importance of halal logo in their purchasing decision - Abdul, Mohani; Yahya, Mastora; Kamarulzaman, Siti Aiesya; Rahman, Mohammad Mizanur (International Organization Of Scientific Research, 2016)
Often the perceptions of Muslim consumers are taken for granted by the Muslim producers and they assume the product will be acceptable among Muslims. Hence, this paper looks into the perception of Muslim consumers in Malaysia on how important has the presence of halal logo on the packaging of food and beverages (F&B). Further, this study investigates how these consumers " perceptions affect their purchasing decision. A total of 1000 sets of self-administered questionnaires were randomly distributed among consumers throughout Malaysia. To achieve the stipulated objectives, the simple mean analysis and factor analysis were performed. The findings revealed that indeed the respondents were very concerned about the halal status of their food, exemplified through the presence of halal logo on the packaging and they were willing to spend more as long as the food are assured halal.